2016
DOI: 10.1080/17470218.2015.1079226
|View full text |Cite
|
Sign up to set email alerts
|

How does the provision of semantic information influence the lexicalization of new spoken words?

Abstract: The integration of a novel spoken word with existing lexical items can proceed within 24 hours of learning its phonological form. However, previous studies have reported that lexical integration of new spoken words can be delayed if semantic information is provided during learning. One possibility is that this delay in lexical integration reflects reduced phonological processing during learning as a consequence of the need to learn the semantic associations. In the current study, adult participants learnt nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
(100 reference statements)
2
5
1
Order By: Relevance
“…Encountering and memorizing a picture of an unfamiliar object might present a significant cognitive load that could detract from the process of encoding the spoken words and hence make word learning more difficult. However, if this were the case, participants should have been worse at learning word-forms paired with unfamiliar objects than word-forms presented in isolation, which, like Hawkins & Rastle (2016), we did not observe. We therefore suggest that our results reflect a positive effect of learning spoken words associated with familiar object pictures rather than difficulties with processing unfamiliar object pictures.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Encountering and memorizing a picture of an unfamiliar object might present a significant cognitive load that could detract from the process of encoding the spoken words and hence make word learning more difficult. However, if this were the case, participants should have been worse at learning word-forms paired with unfamiliar objects than word-forms presented in isolation, which, like Hawkins & Rastle (2016), we did not observe. We therefore suggest that our results reflect a positive effect of learning spoken words associated with familiar object pictures rather than difficulties with processing unfamiliar object pictures.…”
Section: Discussioncontrasting
confidence: 65%
“…Furthermore, retrieval of picture-associated, relative to form-only, novel words showed greater activation of the hippocampal memory system, also suggesting reduced integration into neocortical systems. However, in a behavioural study, Hawkins & Rastle (2016) found equivalent lexical competition from picture-associated and form-only novel words if phonological forms are learned sufficiently well during training. They found that the presence of novel objects during learning did not interfere with lexical competition effects that emerged a week after training, when the training task emphasised phonological form rather than form-meaning learning.…”
Section: Introductionmentioning
confidence: 94%
“…The current findings uniquely show the memory performances of linguistic forms on a single day of learning of linguistic and gustatory stimuli for healthy subjects, while previous studies show the memory performances of linguistic forms on a single day learning or multiple days learning of linguistic and visual, auditory, or haptic stimuli for healthy subjects [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Other research has also reported the learning effects of linguistic and gustatory features for people with word (lexical)-gustatory synesthesia [26] or with autism [21,22].…”
Section: Correlations Between Subjective Evaluations Of Gustatory Features and Performance Of Recognition Memory And Free Recall Phasessupporting
confidence: 49%
“…According to these three levels of processing, the associative learning of the verbal (word forms) and nonverbal stimuli (referents) would be essential to learn real words. Previous studies have reported that word forms can be associated with referents or with words already associated with referents through associative learning, in which participants learned associative pairs of a word form and referent(s), including pictures or sounds (Paivio and Csapo, 1973;Cornelissen et al, 2004;Breitenstein et al, 2005;HultĂ©n et al, 2009;Tsukiura et al, 2010;Tsukiura et al, 2011;Kambara et al, 2013;Takashima et al, 2014;Ferreira et al, 2015;Grönholm et al, 2015;Hawkins et al, 2015;Hawkins and Rastle, 2016;Takashima et al, 2017;Havas et al, 2018;Li et al, 2020;Horinouchi et al, under review;Yan et al, under review;Yang et al, under review) or lexical conditioning (researchers also call the conditioning classical, semantic, or evaluative), in which participants generalize the referents (evaluative responses; e.g., positive and negative meanings) of real words to referents of pseudowords, real words, or symbols (Razran, 1939;Staats and Staats, 1957;Staats and Staats, 1958;Staats et al, 1959a;Staats et al, 1959b;Staats et al, 1961;Paivio, 1964;Cicero and Tryon, 1989;Tryon and Cicero, 1989;Till and Priluck, 2001;Hughes et al, 2018). In the associative learning of word forms in a first language (L1) or a second language (L2) and referents, differences between modalities of referents could affect task performance in the test phase (Lee et al, 2003;Jeong et al, 2010;Carpen...…”
Section: Introductionmentioning
confidence: 99%